Some fixed point theorems for pointwise R-weakly commuting hybrid mappings in metrically convex spaces. - Singh, Amit; Dimri, R.C.; Joshi, Smita (Armenian Journal of Mathematics, 2009)
In the present paper we prove some coincidence common fixed point theorems for a family of hybrid pairs of mappings in metrically convex spaces by using the notion of pointwise R-weakly commuting mappings.